Microstructures and room-temperature compressive properties of Ti6Al4V alloy processed by continuous multistep hydrogenation treatment. (21st September 2020) - Yuan, Baoguo; Du, Jiangfei; Zhang, Xiaoxue; Chen, Qiang; Wan, Yuanyuan; Xing, Zhihui; Zhan, Hong
Abstract: The effects of continuous multistep hydrogenation treatment (CMHT) on the room-temperature compressive properties of Ti6Al4V alloy were investigated through compression tests. The pressure-composition isotherms of Ti6Al4V alloy hydrogenated at 850 °C with different CMHT numbers were also studied. Results show that CMHT number has different effects on microstructures and compressive properties of Ti6Al4V alloy. When CMHT number increased, the amounts of α phase and α′ martensite decreased, the amount of α″ martensite increased first and then decreased, the number of β phase increased. When the CMHT number was one, δ hydrides precipitated at phase boundary. With the increase of CMHT number, δ hydrides precipitated not only at α phase, but also at β phase. The ultimate compression decreased first up to a minimum, and then increased gradually up to a maximum, finally decreased with the increase of CMHT number. The ultimate compression of Ti6Al4V alloy with eight times CMHT increased by 83.83% as compared to the as-received Ti6Al4V alloy, which was the highest ultimate compression among those of all CMHT-treated Ti6Al4V alloys. Reasons for the distinct effects of CMHT number on the room-temperature compressive properties were discussed. Graphical abstract: Image 1 Highlights: The ultimate compression of Ti6Al4V with eight times CMHT increased by 83.83%. Different phases and substructures decided the compressive properties of Ti6Al4V. The hydrogen absorption rate decreased with the increase of CMHT number. The amount of β phase increased with the increase of CMHT number.